Vegetable Filters Reinforced with Fibrillated Cellulose for Iron Removal from Water and Organic White Wines - Sanchez-Poblete, J; Roa-Ruiz, K; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2022)
This work presents an effective and practical alternative for iron removal in aqueous solutions and organic white wines based on continuous filtration via mechanically prepared filters composed of vegetable fibres from Scirpus californicus (Totora) and Gunnera tinctoria (Nalca) and fibrillated cellulose (CF) extracted from Eucalyptus globulus (Eucalipto). These filter materials were characterized by techniques such as Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA). FT-IR signals confirmed that hydroxyl and carboxyl groups were present in the fibres; SEM micrographs showed a compact surface morphology among the three fibres studied; and TGA and DMA identified a thermal improvement and an increase in the compressive strength of the blend after the addition of CF. The effect of the amount of each fibre on iron retention in water and wine was evaluated, and the results showed that filters with 15% CF presented improved iron retention performance. Moreover, the iron retention capacities or efficiencies were 139.4 mg kg −1 and 57.3% in aqueous solution and 26% in white wine using the system composed of 21% GT, 64% SC and 15% CF. These results indicate the potential of these natural fibres in the demetallization of organic wines. © 2021 The Authors